Implementasi Program Penjadwalan CPU Menggunakan Algoritma Round Robin Untuk Penyelesaian Soal Penjadwalan Proses - Syti Salwaa; Ridho Affandi; Shaqila Rahmayani; Zulfahmi Indra (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
In operating systems, CPU scheduling plays a crucial role in determining the execution order of processes to ensure efficient and fair processor utilization. One of the most commonly used scheduling algorithms in time-sharing systems is the Round Robin algorithm. This algorithm works by allocating an equal time slice (time quantum) to each process and then rotating unfinished processes back into the ready queue for subsequent execution. This mechanism makes Round Robin fair and responsive to all processes. This study discusses the implementation of a CPU scheduling program using the Round Robin algorithm in operating systems to solve process scheduling problems. The developed program simulates various process scenarios with different arrival times, burst times, and time quanta to analyze their effects on waiting time and turnaround time. The simulation results indicate that the selection of an appropriate time quantum significantly affects system performance: a too-small time quantum increases the frequency of context switching, while a too-large time quantum reduces system responsiveness. With an optimal time quantum, the Round Robin algorithm achieves a balance between efficiency and fairness in CPU process management, making it highly effective for modern time-sharing operating systems.